A STUDY ON CHANGES OF DIMENSIONAL PROPERTIES OF GREY KNIT FABRIC DUE TO WET PROCESS - Reza, Mohammad Hosain; Ziko, Kanouj Chakma (European Scientific Journal, ESJ, 2015)
Intension of this work was to find out the changes those occur in knit fabric due to wet-process. To study this four single jersey grey knit fabric samples were taken and the properties courses per cm, wales per cm, stitch density, stitch length, tightness factor and G.S.M. were measured. Then they were subjected to go through a full wet-process cycle which is practiced in knit dyeing factories, i.e.; scouring-bleaching, enzyme process, dyeing, wash-off and finishing with softener were done. The samples were then dried and properties courses per cm, wales per cm, stitch density, stitch length, tightness factor and G.S.M. were measured. Finally they were compared with the properties of their respected grey samples. It is very difficult to predict the properties of a knit fabric before they are produced or received a wetprocess treatment. Which leads to difficulties between two sections namely, the knitting section and the finishing section. The authors hope that this work will increase the understandings between the two sections